Copper-catalyzed asymmetric cyclization of alkenyl diynes: method development and new mechanistic insights. Issue 27 (21st June 2021) - Zhu, Xin-Qi; Hong, Pan; Zheng, Yan-Xin; Zhen, Ying-Ying; Hong, Feng-Lin; Lu, Xin; Ye, Long-Wu
Abstract : A copper-catalyzed asymmetric cyclization of alkenyl diynes involving a vinylic C(sp 2 )–H functionalization is reported, enabling the construction of various valuable chiral polycyclic-pyrroles in high yields and enantioselectivities. Abstract : Metal carbenes have proven to be one of the most important and useful intermediates in organic synthesis, but catalytic asymmetric reactions involving metal carbenes are still scarce and remain a challenge. Particularly, the mechanistic pathway and chiral induction model in these asymmetric transformations are far from clear. Described herein is a copper-catalyzed asymmetric cyclization of alkenyl diynes involving a vinylic C(sp 2 )–H functionalization, which constitutes the first asymmetric vinylic C(sp 2 )–H functionalization through cyclopentannulation. Significantly, based on extensive mechanistic studies including control experiments and theoretical calculations, a revised mechanism involving a novel type of endocyclic copper carbene via remote-stereocontrol is proposed, thus providing new mechanistic insight into the copper-catalyzed asymmetric diyne cyclization and representing a new chiral control pattern in asymmetric catalysis based on remote-stereocontrol and vinyl cations. This method enables the practical and atom-economical construction of an array of valuable chiral polycyclic-pyrroles in high yields and enantioselectivities.